Impact of Mixture Ratio on Bio-Composite Material from Bamboo and Recycled Polyethylene Terephthalate (PET) - Ojetoye, Abiodun Ayodeji; Ilori, Olutosin Olufisayo; Iwedi, Shalom Chitom; Obiechefu, Kelechi Valentine; Okezue, Precious Arinze; Feranmi, Kareem (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
The study investigated the impact of mixture ratio on various physico-chemical and mechanical properties of a bio-composite material made from bamboo and recycled polyethylene terephthalate (PET). The bamboo and recycled PET bottles were sourced from Adeleke University, Ede research farm and waste buckets in male hostels of the same university, respectively. The weight percentages (wt%) of bamboo and PET powder were adjusted as follow: 60 wt% bamboo and 40 wt% PET, 65 wt% bamboo and 35 wt% PET, 70 wt% bamboo and 30 wt% PET, 75 wt% bamboo and 25 wt% PET, and 80 wt% bamboo and 20 wt% PET, respectively. The findings indicate that as the mixture ratio of the constituents varied, the composite samples exhibited a decrease in density (from 915.45 – 819.24 kg/m3), flammability (from 25.84 – 19.93 s), hardness (from 88.55 – 55.57 BHN), compressive strength (from 14.78 – 9.10 N/mm3), and wear resistance (from 0.0096 – 0.0011 cm/cm3). In contrast, the composite exhibited an increase in oil and water absorption rates ranging from 0.0010% to 0.0810% and from 0.0112% to 0.12%, respectively, as the mixture ratio varied. Furthermore, the ratio of the mixture does not impact the acidity or alkalinity of the resulting composite material. Hence, the mixture ratio that yields optimal attributes result in excellent performance, tailored to the specific requirements of industries such as automotive and aeronautics. Finally, the diverse combination of bamboo and PET powders provides a practical approach to creating efficient, environmentally-friendly bio-composite materials suitable for various industrial applications.